2021
DOI: 10.3390/vaccines9121499
|View full text |Cite|
|
Sign up to set email alerts
|

Nasal and Salivary Mucosal Humoral Immune Response Elicited by mRNA BNT162b2 COVID-19 Vaccine Compared to SARS-CoV-2 Natural Infection

Abstract: SARS-CoV-2 antibody assays are crucial in managing the COVID-19 pandemic. Approved mRNA COVID-19 vaccines are well known to induce a serum antibody responses against the spike protein and its RBD. Mucosal immunity plays a major role in the fight against COVID-19 directly at the site of virus entry; however, vaccine abilities to elicit mucosal immune responses have not been reported. We detected anti-SARS-CoV-2 IgA-S1 and IgG-RBD in three study populations (healthy controls, vaccinated subjects, and subjects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 43 publications
4
49
1
Order By: Relevance
“…We observed no increase in anti-S1 and anti-RBD IgA levels. In contrast, some studies did show a mucosal IgA response,27 28 although this was often weaker than the mucosal IgG and systemic antibody response. However, some other studies also reported no mucosal IgA response following vaccination 29 30…”
Section: Discussionmentioning
confidence: 87%
“…We observed no increase in anti-S1 and anti-RBD IgA levels. In contrast, some studies did show a mucosal IgA response,27 28 although this was often weaker than the mucosal IgG and systemic antibody response. However, some other studies also reported no mucosal IgA response following vaccination 29 30…”
Section: Discussionmentioning
confidence: 87%
“…We have not measured the presence of SARS‐CoV‐2‐specific IgG and IgA in other mucosal fluids. However, two recent publications show that SARS‐CoV‐2‐specific IgG and IgA are both detected also in nasal fluid samples (Chan et al , 2021; Guerrieri et al , 2021), even though at lower levels than in the saliva (Guerrieri et al , 2021). The fact that SARS‐CoV‐2‐specific IgA2 were not detected in the saliva of vaccinated subjects supports the need for mucosal vaccination and/or boosting strategies that promote anti‐SARS‐CoV‐2 S‐IgA, which are more potent at neutralizing the virus than IgGs thanks to their mechanism of pathogen clearance called immune exclusion (Mantis et al , 2011; Wang et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…First, we have not yet developed appropriate assays for mucosal immune responses to deepen our understanding of the immune advantage of aerosolized Ad5-nCoV. Saliva IgA antibodies were detected in some BNT162b2 vaccine recipients (25, 26) , but whether IgA was exuded from serum or produced by a local mucosal immune response could not be determined. More assays need to be developed to analyze local mucosal immune responses, including secretory IgA antibodies and local cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…First, we have not yet developed appropriate assays for mucosal immune responses to deepen our understanding of the immune advantage of aerosolized Ad5-nCoV. Saliva IgA antibodies were detected in some BNT162b2 vaccine recipients (25,26) Boosters probably increase vaccine effectiveness against infection with and transmission of the SARS-CoV-2 Omicron variant.…”
Section: Discussionmentioning
confidence: 99%